Designing clinical trials in paediatric inflammatory bowel diseases: a PIBDnet commentary. Issue 1 (12th April 2019) - Turner, Dan; Griffiths, Anne M; Wilson, David; Mould, Diane R; Baldassano, Robert N; Russell, Richard K; Dubinsky, Marla; Heyman, Melvin B; de Ridder, Lissy; Hyams, Jeffrey; Martin de Carpi, Javier; Conklin, Laurie; et al.
Abstract : Introduction: The optimal trial design for assessing novel therapies in paediatric IBD (PIBD) is a subject of intense ongoing global discussions and debate among the different stakeholders. However, there is a consensus that the current situation in which most medications used in children with IBD are prescribed as off-label without sufficient paediatric data is unacceptable. Shortening the time lag between adult and paediatric approval of drugs is of the upmost importance. In this position paper we aimed to provide guidance from the global clinical research network (Pediatric Inflammatory Bowel Disease Network, PIBDnet) for designing clinical trials in PIBD in order to facilitate drug approval for children. Methods: A writing group has been established by PIBDnet and topics were assigned to different members. After an iterative process of revisions among the writing group and one face-to-face meeting, all statements have reached consensus of >80% as defined a priori. Next, all core members of PIBDnet voted on the statements, reaching consensus of >80% on all statements. Comments from the members were incorporated in the text. Results: The commentary includes 18 statements for guiding data extrapolation from adults, eligibility criteria to PIBD trials, use of placebo, dosing, endpoints and recommendations for feasible trials. Controversial issues have been highlighted in the text. Conclusion: The viewpoints expressed in this paper could assist planning clinical trials in PIBD which are both of high quality and ethical, while remaining pragmatic.